Pharmacoeconomic study of antimicrobial control flow adoption by clinical pharmacy of a university hospital - Pereira, Bárbara Rebeca Alves (2022)
Currently antimicrobial resistance is a serious threat to public health. The increase in the incidence of infections by multidrug-resistant organisms has become a focus of concern regarding patient safety throughout the care cycle. The aim of this study was to evaluate the impact of the implementation of a new flow of antimicrobial dispensing and control in a university hospital. An observational and retrospective descriptive study was conducted with a quantitative approach, characterized as a pharmacoeconomic analysis, in one of the hospitalization posts of the University Hospital (HU) of the Federal University of Piauí (UFPI), located in Teresina, Piauí. A reduction in consumption was observed in 9 of the 12 most prescribed antimicrobials after the implementation of the dispensing flow, except for three antimicrobials, Ciprofloxacin 2mg/ml, Metronidazole 500mg/100ml and Vancomycin 500mg. Before the implementation of the flow, the 12 most prescribed antimicrobials implied 93% of the ATB consumed in the hospital, representing only 76% after the appropriate pharmaceutical interventions, demonstrating efficiency of the methodology adopted. The 12 tMDs most prescribed represented a cost of 98% of the hospital's expenses with antimicrobials, which now represents only 51% of the expenses with these. The reduction in costs observed in the period 2021 compared to 2020 may be directly related to the performance of hospital pharmacists in partnership with multidisciplinary teams and CCIH. The relationship between pharmacoeconomics and the rational use of antimicrobials is evident, so that the consumption of antimicrobials directly affects the costs generated in the hospital.